Helmintos de la República de Costa Rica XIII. Algunos tremátodos de Rana pipiens. Descripción de Glypthelmins facioi n. sp. - Brenes, Rodrigo Ramón (1959)
In the present paper the presence of Megalodiscus temperatus and Cepbalogonimus americanus is reported from Rana pipiens and a new species of trematod, Glypbtelmins facioi, is described from the same host.